Stellar kinematics of dwarf galaxies from multi-epoch spectroscopy: application to Triangulum II. Issue 2 (30th May 2022) - Buttry, Rachel; Pace, Andrew B; Koposov, Sergey E; Walker, Matthew G; Caldwell, Nelson; Kirby, Evan N; Martin, Nicolas F; Mateo, Mario; Olszewski, Edward W; Starkenburg, Else; Badenes, Carles; Daher, Christine Mazzola
ABSTRACT: We present new MMT/Hectochelle spectroscopic measurements for 257 stars observed along the line of sight to the ultrafaint dwarf galaxy Triangulum II (Tri II). Combining results from previous Keck/DEIMOS spectroscopy, we obtain a sample that includes 16 likely members of Tri II, with up to 10 independent redshift measurements per star. To this multi-epoch kinematic data set, we apply methodology that we develop in order to infer binary orbital parameters from sparsely sampled radial velocity curves with as few as two epochs. For a previously identified (spatially unresolved) binary system in Tri II, we infer an orbital solution with period 296.0_-3.3^+3.8 d, semimajor axis 1.12^+0.41_-0.24 au, and systemic velocity -380.0 ± 1.7 km s^-1 that we then use in the analysis of Tri II's internal kinematics. Despite this improvement in the modelling of binary star systems, the current data remain insufficient to resolve the velocity dispersion of Tri II. We instead find a 95 per cent confidence upper limit of σ _v 3.4 km s^-1 .